2010
DOI: 10.2478/v10182-010-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Ocimum kilimandscharicum Guerke (Labiatae)

Abstract: An efficient plant regeneration protocol has been developed from nodal explants of Ocimum kilimandscharicum Guerke, a medicinally important herbaceous plant species belonging to the family Lamiaceae. Axillary shoot bud proliferation was initiated from nodal explants cultured on MS medium supplemented with various concentrations of 6-benzyladenine (BA) (0.5-3.0 mg/l), kinetin (KN) (0.5-3.0 mg/l) and 2-isoPentenyladenine (2-iP) (0.5-3.0 mg/l). The maximum number of shoots (6.09±0.05), with average length 3.83±0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…This would exponentially increase the number of plantlets obtainable in each cycle. An increase of axillary shoots in consecutive excision-subculture cycles has also been reported in Ocimum kilimandscharicum recently (Saha et al, 2010).…”
Section: Resultssupporting
confidence: 55%
“…This would exponentially increase the number of plantlets obtainable in each cycle. An increase of axillary shoots in consecutive excision-subculture cycles has also been reported in Ocimum kilimandscharicum recently (Saha et al, 2010).…”
Section: Resultssupporting
confidence: 55%
“…Full strength MS medium containing auxins showed very poor response in rooting, but well developed roots were achieved on half strength MS medium supplemented with NAA, IBA & IAA and with reduce sucrose concentration (2%) gave us well developed roots within 12 -15 days. In many species such as Lavandula vera [51)], Ocimum kilimandscharicum [52], rooting frequency was higher when shoots were rooted on low strength MS medium. The rational behind the favorable effect of reduced macronutrient concentration is that the concentration of nitrogen ions needed for root formation is much lower than for shoot formation and growth [53].…”
Section: Effect Of Auxinmentioning
confidence: 99%
“…There are many reports on molecular characterization of micropropagated plants by the RAPD technique especially to confirm the clonal fidelity and genetic stability among tissue culture grown plants and donor [52,[63][64][65][66]. Because RAPD analysis is particularly well suited to high output system required for plant breeding, it is easy to perform, fast, reliable and of relatively low cost [67].…”
Section: Molecular Analysismentioning
confidence: 99%
“…Sahoo et al (1997) and Saha et al (2010) stated that root de ve lop ment was getting delayed on higher IBA, NAA and IAA concentration containing medium. They further said that at the same time the callus formation took place at the base of the shoots of some other plant species (Sahoo et al 1997, Saha et al 2010. Similarly, reported that the higher concentrations of IBA, NAA and IAA resulted in swelling and callus formation at the base of the shoots of C. odorata and C. maccannii.…”
Section: Discussionmentioning
confidence: 99%